Study of Effectiveness Longan Seed as Natural Coagulants for Textile Wastewater Treatment - Kamarulzaman, Nur Atiqah Alya; Mawarni Jamaluddin,; Nurul Iman Othman,; Norhayati Ngadiman, (Multidisciplinary Applied Research and Innovation, 2025)
This research investigates the coagulation efficacy of longan seed powder as a natural coagulant in treating textile wastewater that contains dangerous pollutants. The experiments were conducted at the laboratory level after analysing the properties and morphology of longan seed powder with the help of X-ray diffraction (XRD) and scanning electron microscopy (SEM). The potential for dry longan seed powder to act as a coagulant is investigate to treat textile wastewater within a range of concentrations of NaCl solution. The removal efficiency of the coagulation process is also tested for different masses of longan seed powder. The raw material of longan seeds was ground into a powder and mixed with sodium chloride (NaCl) and distilled water to produce NaCl concentrations. The initial data taken were turbidity, pH, COD, and color to determine the effectiveness of longan seeds as natural coagulants in textile wastewater. X-ray diffraction (XRD) was used to characterize the crystalline structure of longan seeds while scanning electron microscopy (SEM) was employed to measure the size and shape of the seeds.  A proper characterization of the longan seeds was applied using the X-ray diffraction (XRD) technique, which showed the crystalline patterns of polyphenolic compounds and minerals. This study shows that among four different concentration solvents, 0.5 mol NaCl is the most optimum condition for longan seed results in textile wastewater. Moreover, the finding of this study is that longan seeds can treat textile wastewater by reducing the dosage required in the process of treating textile wastewater until an optimal result is achieved. In conclusion, it is substantiated by the present study that a natural coagulant prepared from longan seeds can be effective for the treatment of textile wastewater. In addition, it benefits by promoting sustainable waste management practices, offering a cost-effective alternative for wastewater treatment, and reducing environmental contamination risks.